KETANGGUHAN MENGHADAPI MEGATHRUST: EVALUASI STRATEGIS PROGRAM EDUKASI MITIGASI BENCANA DAN BANTUAN HIDUP DASAR PADA GENERASI MUDA DI ZONA SUBDUKSI SULAWESI UTARA - Taufiq Qurrohman; Zuhriana K Yusuf; Azizah Nur Ain Putri; Nurhaliza Shaumty; Tesya Gamananda Puluhuwala; Aliffa Cahya Potutu; Siti Maghfirah Ekie; Fadillah Syabania Ishak (Journal of Community Services on Multidisciplinary Sciences, 2026)
This study evaluates a community service program focusing on megathrust earthquake mitigation and basic life support education at SMA Negeri 3 Gorontalo. Located in the North Sulawesi subduction zone, Gorontalo faces  significant seismic risks. Using a quasi-experimental design, 75 students participated in simulation-based learning and clinical skills training. Results showed a significant transformation in knowledge regarding specific megathrust hazards and improved psychomotor responses during evacuation drills. Furthermore, students successfully acquired basic life support skills, including cardiopulmonary resuscitation and splinting. The study concludes that simulation based education effectively enhances disaster resilience among adolescents. Recommendations include integrating local curriculum and conducting periodic simulations to ensure sustainability.